MySQL Administrator's Bible - Cabral, Sheeri (Wiley Publishing, 2011)
With special focus on the next major release of MySQL, this resource provides a solid framework for anyone new to MySQL or transitioning from another database platform, as well as experience MySQL administrators. The high-profile author duo provides essential coverage of the fundamentals of MySQL database management—including MySQL’s unique approach to basic database features and functions—as well as coverage of SQL queries, data and index types, stores procedure and functions, triggers and views, and transactions. They also present comprehensive coverage of such topics as MySQL server tuning, managing storage engines, caching, backup and recovery, managing users, index tuning, database and performance monitoring, security, and more.